Arthropod arbiters: natural enemy communities mediate the effects of landscape and local-scale complexity on Lygus-induced crop loss in organic strawberries - Lu, Adrian; Gonthier, David; Sciligo, Amber; Garcia, Karina; Chiba, Taiki; Juárez, Gila; Kremen, Claire (Frontiers in Sustainable Food Systems, 2024)
Sustainable pest management requires growers and regional land managers to consider the relationships among pest management practices, pest and natural enemy communities, crop loss, and multi-scalar habitat complexity. However, the causal links among these variables, in particular potential interactions between landscape and local-scale habitat complexity, remain underexplored. In the context of organically managed strawberry crops in California’s Central Coast, we tested the independent effects of landscape and local habitat complexity gradients on arthropod communities and crop loss using a piecewise structural equation model (PSEM). We found that landscape-scale woody habitat proportion indirectly decreased crop loss through its positive effect on natural enemy abundance, while grassland proportion had the opposite effect due to its association with an important strawberry pest (Lygus spp.). We detected a pattern suggesting that on-farm diversification practices are most effective at reducing crop loss at an intermediate level (26%) of woody habitat proportion. Both organic-compliant insecticide application and tractor vacuuming negatively impacted natural enemies, and therefore had qualified effects on crop loss. Our study shows the key roles of native woodlands and natural enemy communities in reducing crop loss and highlights the importance of managing habitat complexity at both landscape and local scales.